Jika rakyat berkuasa : upaya membangun masyarakat madani dalam kultur feodal - Rais, M. Amien; Tim MAULA (Bandung : Pustaka Hidayah, 1999)
Collection of articles on democracy, politics, and Indonesian political leadership
Includes bibliographical references and index
Keywords: Political leadership -- Indonesia; Democracy -- Indonesia; Indonesia -- Politics and government -- 1998-